2017
DOI: 10.31357/vjm.v3i1.3639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perceived Desirability, Perceived Feasibility and Performance Expectancy on Use of IT Innovation: Technology Adoption Decisions and Use Behaviour

Abstract: Theoretical perspectives from the field of entrepreneurship can be used to examine entrepreneurs’ intention to use IT innovations. This study collected 412 completed survey responses from entrepreneurs and used structural equation modelling to test the proposed technology acceptance decision model. The results showed the significant effect of perceived desirability, perceived feasibility and performance expectancy as the salient antecedents of intention to adopt and use IT innovation. This study examined the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The framework suggested that consumer subjective expectations of technology attributes and use experiences are based on perceived desirability and feasibility in the context of technology acceptance (Jia et al., 2012). Researchers argue that individuals use or adopt a new technology when they feel that it provides value and is attractive (desirability) and when they feel that they are personally capable of performing a set of tasks by using it (feasibility) (Jia et al., 2012; Jin & DeVaney, 2011; Moghavvemi et al., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework suggested that consumer subjective expectations of technology attributes and use experiences are based on perceived desirability and feasibility in the context of technology acceptance (Jia et al., 2012). Researchers argue that individuals use or adopt a new technology when they feel that it provides value and is attractive (desirability) and when they feel that they are personally capable of performing a set of tasks by using it (feasibility) (Jia et al., 2012; Jin & DeVaney, 2011; Moghavvemi et al., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceived desirability refers to expected “value from completion of an (prospective) action” (Jia et al., 2012, p. 211). In the context of technology adoption, desirability represents consumer expectations of benefits of using technology; thus, it describes the degree of favorability and attraction an individual perceives toward its use (Moghavvemi et al., 2017). Consumer experiences are integrative in nature because they process multiple values derived from a variety of needs and wants at any given moment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2003) and the technology acceptance model (TAM) (Davis and Davis, 1989) is the intention that impacts the use or adoption of technology. Prevailing empirical literature proves that the E-HRM intention impacts the E-HRM use or adoption (Moghavvemi, 2017; Giri et al. , 2019).…”
Section: Results and Findingsmentioning
confidence: 99%
“…, 2019). The desire or willingness for E-HRM is the intention (Davis and Davis, 1989; Moghavvemi, 2017; Giri et al. , 2019), whereas the decision to use or launch E-HRM is referred to as the E-HRM adoption.…”
Section: Results and Findingsmentioning
confidence: 99%
See 1 more Smart Citation